Modulatory Action by the Serotonergic System: Behavior and Neurophysiology in Drosophila melanogaster - Zana R. Majeed; Esraa Abdeljaber; Robin Soveland; Kristin Cornwell; Aubrey Bankemper; Felicitas Koch; Robin L. Cooper (Neural Plasticity)
Serotonin modulates various physiological processes and behaviors. This study investigates the role of 5-HT in locomotion and feeding behaviors as well as in modulation of sensory-motor circuits. The 5-HT biosynthesis was dysregulated by feeding Drosophila larvae 5-HT, a 5-HT precursor, or an inhibitor of tryptophan hydroxylase during early stages of development. The effects of feeding fluoxetine, a selective serotonin reuptake inhibitor, during early second instars were also examined. 5-HT receptor subtypes were manipulated using RNA interference mediated knockdown and 5-HT receptor insertional mutations. Moreover, synaptic transmission at 5-HT neurons was blocked or enhanced in both larvae and adult flies. The results demonstrate that disruption of components within the 5-HT system significantly impairs locomotion and feeding behaviors in larvae. Acute activation of 5-HT neurons disrupts normal locomotion activity in adult flies. To determine which 5-HT receptor subtype modulates the evoked sensory-motor activity, pharmacological agents were used. In addition, the activity of 5-HT neurons was enhanced by expressing and activating TrpA1 channels or channelrhodopsin-2 while recording the evoked excitatory postsynaptic potentials (EPSPs) in muscle fibers. 5-HT2 receptor activation mediates a modulatory role in a sensory-motor circuit, and the activation of 5-HT neurons can suppress the neural circuit activity, while fluoxetine can significantly decrease the sensory-motor activity.